ARE MILENIALS AND GENERATION Z STILL INTERESTED IN ENTERPRISES POST COVID? - Axel Leonardo Valentino; Chrisanty V. Layman (Universitas Pelita Harapan, 2023)
Entrepreneurial intention is a bridge to start entrepreneurial activity. Increasing entrepreneurial activity in society will help improve the economy, standard of living and welfare of the community. The millennial and z generations, which are the generations with the largest population in Indonesia, play an important role in this regard. The purpose of this research is to find out what factors can influence entrepreneurial intentions in the millennial and z generations in Indonesia. The results of this research data sample are 277 respondents who are individuals belonging to the millennial generation and z generation. The sample respondent data that was successfully collected was then tested using the SmartPLS 4 application to find out the results of the validity, reliability and hypothesis testing results. The results of testing the hypothesis in this study indicate that family support has a positive effect on subjective norms, perceived behavioral control, and dominance. Then the relationship between perceived behavioral control and entrepreneurial intentions through mediating attitudes towards entrepreneurship and the relationship between family support and entrepreneurial intentions through mediation of perceived behavioral control and attitudes towards entrepreneurship proves to be positive. Meanwhile, subjective norms and dominance do not have a positive effect on entrepreneurial intentions through the same mechanism.Bahasa Indonesia Abstrak: Intensi kewirausahaan merupakan jembatan untuk dimulainya aktivitas kewirausahaan. Dengan meningkatnya aktivitas kewirausahaan di masyarakat akan membantu meningkatkan perekonomian, taraf hidup dan kesejahteraan masyarakat. Generasi milenial dan generasi Z yang merupakan generasi dengan jumlah populasi paling banyak di Indonesia memainkan peranan penting dalam hal ini. Tujuan dari penelitian untuk mengetahui faktor-faktor apa saja yang dapat mempengaruhi intensi kewirausahaan pada generasi milenial dan generasi Z di Indonesia. Hasil sampel data penelitian ini yaitu 277 responden yang merupakan individu yang tergolong ke dalam generasi milenial dan generasi Z. Sampel data responden yang berhasil dikumpulkan kemudian dilakukan pengujian dengan menggunakan aplikasi SmartPLS 4 untuk mengetahui hasil uji validitas, reliabilitas, dan hasil uji hipotesis. Hasil pengujian hipotesis pada penelitian ini menunjukkan bahwa dukungan keluarga berpengaruh positif terhadap norma subjektif, perceived behavioural control, dan dominance. Kemudian hubungan antara perceived behavioural control dan intensi kewirausahaan melalui mediasi sikap terhadap kewirausahaan serta hubungan antara dukungan keluarga dan intensi kewirausahaan melalui mediasi perceived behavioural control dan sikap terhadap kewirausahaan terbukti positif. Sedangkan norma subjektif serta dominance tidak berpengaruh secara positif terhadap intensi kewirausahaan melalui mekanisme yang sama.